Транскордонне співробітництво ЄС в рамках реалізації проектів STORK та STORK 2.0 - Михалюк, Н. Ю.; Mykhaliyk, N.Y. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The article explores the principles and concepts of STORK and STORK 2.0 projects, their impact and importance for today's EU activities. Reviewed the main program, pilot projects and peculiarity of their activities within the program. Ascertained the connection with other EU programs, analyzes its special features.
EU cross-border cooperation within STORK and STORK 2.0 framework
Н.Ю. Михалюк, аспірант Східноєвропейського національного університету імені Лесі Українки Науковий керівник: к.геог.н., доц. СНУ ім. Лесі Українки Федонюк С. В. (Україна, м.Луцьк)
Keywords: cross-border cooperation; eGovernment; STORK; STORK 2.0; electronic systems interoperability; electronic identity card; eID